Some aspects of the autecology of Ocotea Bullata (Burch.) Baillon (Lauraceae), with emphasis on response to certain stress factors - Lubbe, Willem Alwyn (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1989.